Nutrition for football: The FIFA/F-MARC consensus statement (2005)
Football players can stay healthy, avoid injury and achieve their performance goals by adopting good dietary habits. Players should choose foods that support consistent, intensive training and optimise match performance. What a player eats and drinks in the days and hours before a game, as well as during the game itself, can influence the result by reducing the effects of fatigue and allowing players to make the most of their physical and tactical skills. Food and fluid taken soon after a game and training can optimise recovery. All players should have a nutrition plan that takes account of individual needs. The energetic and metabolic demands of football training and match play vary across the season, with the level of competition and with individual characteristics. Typical energy costs of training or match play in elite players are about 6 MJ (1500 kcal) per day for men and about 4 MJ (1000 kcal) for women. The football player should eat a wide variety of foods that provide sufficient carbohydrate to fuel the training and competition program, meet all nutrient requirements, and allow manipulation of energy or nutrient balance to achieve changes in lean body mass, body fat or growth. Low energy availability causes disturbances to hormonal, metabolic and immune function and to bone health. An adequate carbohydrate intake is the primary strategy to maintain optimum function. Players may need 5-7 grams of carbohydrate per kg body mass during periods of moderate training and up to about 10 g/kg during intense training or match play.